Turkey's water diplomacy : analysis of its foundations, challenges and prospects - Kibaroğlu, Ayșegül (Science diplomacy: managing food, energy and water sustainably., 2021)
"Turkey's Water Diplomacy presents the legal and institutional foundations of Turkey's water diplomacy within its historical and geographical contexts. It analyses the evolving position of Turkey vis-à- vis the international water law. Delineating actors and processes in transboundary water policy-making, Turkey's Water Diplomacy utilizes the Water Diplomacy Framework in making policy-relevant recommendations for tackling future challenges in Turkey's water diplomacy."--